Reversion in Polyoma-transformed Cells: Retransformation, Induced Antigens and Tumorigenicity - Marin, G. (1969)
We studied the properties of two morphologically reverted cell clones isolated as chromosomal segregants from a “hybrid” clone of BHK 21/13 hamster fibroblasts, transformed with polyoma virus. Both clones were less tumorigenic than control transformed cells. They contained no detectable polyoma-specific complement-fixing antigen. Induced transplantation antigen also appeared to be lost or reduced. Both clones could be retransformed with polyoma virus, suggesting that their reversion is due to the loss of viral genes from the transformed cell.